Benzo[k]fluoranthene-induced changes in miRNA-mRNA interactions in human hepatocytes - Song, M.-K.; Song, M.; Choi, H.-S.; Ryu, J.-C. (Kluwer Academic Publishers, 2012)
Toxicology studies assessing the risk of environmental toxicants in humans frequently use in vitro systems in combination with transcriptomics to characterize toxic responses. Thus far, changes have mostly been investigated at the mRNA level. Recently, microRNAs (miRNAs) have attracted attention because they are powerful negative regulators of mRNA levels and thus may be responsible for the modulation of important mRNA networks implicated in toxicity. This study aimed to identify possible miRNA-mRNA networks as novel interactions at the gene expression level after exposure to environmental toxicants. Benzo[k]fluoranthene (BF), a polycyclic aromatic hydrocarbon that is ubiquitously distributed throughout the environment, was used. We analyzed mRNA and miRNA profiles in HepG2 cells, a human liver cell line, using a human oligonucleotide chip. Changes in miRNA expression in response to BF, in combination with multiple alterations of mRNA levels, were observed. Many of the altered mRNAs were targets of altered miRNAs. Using gene ontology (GO) and KEGG pathway analysis, we determined the relevance of such miRNA deregulation to carcinogenicity. This revealed five miRNAs that appear to participate in specific BFresponsive pathways relevant to genotoxicity and carcinogenicity, such as DNA damage repair, apoptosis, cancer, VEGF signaling, and Jak-STAT signaling. Our results indicate that miR-146a, miR-365, let-7f, miR-199b-5p, and miR-30c-1* are novel players in the BF response. Therefore, this study demonstrates the added value of an integrated miRNA-mRNA approach for identification of the molecular mechanisms induced by BF in an in vitro human model. ？ 2012 Korean Society of Environmental Risk Assessment and Health Science and Springer Science+Business Media Dordrecht.
Keywords: benzo [k] fluoranthene; Janus kinase; messenger RNA; microRNA; STAT protein; unclassified drug; vasculotropin; apoptosis; article; carcinogenicity; cell survival; cell viability; controlled study; DNA microarray; DNA repair; down regulation; exposure; gene expression; gene regulatory network; genotoxicity; human; human cell; liver cell; liver cell carcinoma; RNA binding; signal transduction; upregulation